Solubility modelling and thermodynamic dissolution functions of phthalimide in ten organic solvents. (March 2016) - Xu, Renjie; Wang, Jian; Han, Shuo; Du, Cunbin; Meng, Long; Zhao, Hongkun
Graphical abstract: Highlights: The solubility of phthalimide in ten organic solvents were determined. The solubility were correlated with four thermodynamic models. The dissolution thermodynamic properties of solution were obtained. Abstract: In this work, a high performance liquid chromatography (HPLC) was employed to determine the solubilities of phthalimide in methanol, isopropanol, n -propanol, ethyl acetate, acetonitrile, i -butanol, n -butanol, toluene, acetone and ethanol at temperatures ranging from (283.15 to 318.15) K under 0.1 MPa. The solubility of phthalimide in a fixed solvent increases with an increase in temperature. At a certain temperature, the solubility in different solvents decreases according to the following order: acetone > ethyl acetate > (methanol, isopropanol, n -propanol, acetonitrile, i -butanol, n -butanol, ethanol) > toluene. Four models, modified Apelblat equation, λh equation, Wilson model and NRTL model were employed to correlate the solubility of phthalimide in the solvents studied. The evaluated solubilities provide better agreement with the modified Apelblat equation than the other three models. The four thermodynamic models are all acceptable for correlating the solubility of phthalimide in the solvents studied. Furthermore, the standard dissolution enthalpy and excess enthalpy of the solutions were obtained. The dissolution process of phthalimide in the selected solvents is discussed.